2021
DOI: 10.1038/s41598-021-84996-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in marital status and survival in women with breast cancer: a population-based study

Abstract: Marital status proved to be an independent prognostic factor for survival in patients with breast cancer. We therefore strove to explore the impact of dynamic changes in marital status on the prognosis of breast cancer patients. We selected patients meeting the eligibility criteria from the Surveillance, Epidemiology, and End Results cancer database. We then used multivariate Cox proportional hazard regression model to analyze the effect of dynamic changes in marital status on the prognosis of overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
1
22
1
Order By: Relevance
“…Previous studies have shown that marriage was a predictor of breast cancer survival, both in early and late stages. [25][26][27] And our study found a 1.17-fold increase in the risk of death for those without a partner at diagnosis, which was fully consistent with the finding (HR = 1.18) of Hinyard L et al 25 The absence of a spouse may have many impacts on patient psychology, finances, support, and care, especially in elderly LABC, which can lead to barriers to their treatment. 21 , 25-27 In addition, WP Tew et al also supported the use of molecular subtypes, T and N stage as treatment selection criteria.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that marriage was a predictor of breast cancer survival, both in early and late stages. [25][26][27] And our study found a 1.17-fold increase in the risk of death for those without a partner at diagnosis, which was fully consistent with the finding (HR = 1.18) of Hinyard L et al 25 The absence of a spouse may have many impacts on patient psychology, finances, support, and care, especially in elderly LABC, which can lead to barriers to their treatment. 21 , 25-27 In addition, WP Tew et al also supported the use of molecular subtypes, T and N stage as treatment selection criteria.…”
Section: Discussionsupporting
confidence: 90%
“…Although the needs of breast cancer patients can be partially provided by their children and relatives, not all of them can be provided. In unmarried patients, the marriage after the breast cancer diagnosis also has the positive impact on the survival 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Divorce was suggested as an independent prognostic factor for survival among breast cancer patients (Chen et al, 2015;Li et al, 2015;Qiu et al, 2016). In a recent cohort study, involving patients above 20 years who were diagnosed with stages I-III primary breast cancer and who received surgical treatment from 1992 to 2015, the divorced group (N = 3,044) exhibited a higher risk of breast cancer-specific death (HR 1.11, 95% CI: 1.05, 1.18, p < 0.001) and all-cause death (HR 1.27, 95% CI: 1.22, 1.32, p < 0.001) than the group that remained married (N = 17,623) (Ding et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…Although divorce affects many aspects of a couple's life (Chen et al, 2015;Li et al, 2015;Qiu et al, 2016;Ding et al, 2021), only few empirical studies have found an association between divorce and quality of life (QoL). Previous studies have provided information on marital status soon after the diagnosis of breast cancer, and thus may not reflect the dynamic changes in longterm survival populations or account for marital status changes before or after the cancer diagnosis (Ding et al, 2021). Moreover, research on the relation between marital status and health outcomes among cancer patients has generally used the Surveillance, Epidemiology, and End Results (SEER) cancer database or other national surveys, which elicited limited information on QoL (Abdollah et al, 2011;Aizer et al, 2013;Ding et al, 2021).…”
Section: Introductionmentioning
confidence: 99%